Propensity-matched analysis of the efficacy of olanexidine gluconate versus chlorhexidine-alcohol as an antiseptic agent in thoracic esophagectomy - Takeo Fujita; Naoya Okada; Takuji Sato; Kazuma Sato; Hisashi Fujiwara; Takashi Kojima; Hiroyuki Daiko (BMC Surgery, 2022)
Abstract Background In the present matched-cohort study, we investigated the efficacy of olanexidine gluconate in comparison with chlorhexidine-alcohol as an antiseptic agent in thoracic esophagectomy. Methods A total of 372 patients with esophageal cancer who were scheduled to undergo thoracic esophagectomy between 2016 and 2018 were assigned to one of two groups based on the preoperative antiseptic agent used in thoracic esophagectomy. We investigated the incidence of surgical site infectious complications in the propensity-matched cohort. Results Based on the propensity score, 116 patients prepared with 1.5% olanexidine gluconate and 114 patients prepared with 1.0% chlorhexidine-alcohol as surgical skin antisepsis were selected. No significant intergroup differences were observed with respect to incisional surgical site infection (0.8% in the olanexidine group versus 0.8% in the chlorhexidine group) and deep fascial/organ space surgical site infection (1.7%/10.3% in the olanexidine group versus 3.5%/15.7% in the chlorhexidine group, p = 0.39/p = 0.03). Notably, the respective incidences of surgical site infection except anastomotic leakage were 1.7% and 7.0% in the olanexidine and chlorhexidine groups (p = 0.04). Conclusions Olanexidine gluconate was well tolerated and significantly reduced incidence of surgical site infection except anastomotic leakage in comparison with chlorhexidine-alcohol as an antiseptic agent in thoracic esophagectomy with three-field lymph node dissection.